PENGARUH INTERVENSI TERAPI MUSIK KLASIK TERHADAP TEKANAN DARAH DAN KUALITAS TIDUR PADA LANSIA PENDERITA HIPERTENSI DIRUANG HEMODIALISA - Nopriani, Yora; Xesti, Ecy (Jurnal Kesehatan dan Pembangunan, 2025)
An elderly person is someone who has reached the age of 60 years and above and whose body is increasingly susceptible to diseases such as hypertension and sleep disorders. One effort to address these problems is through the use of classical music therapy. The purpose of this study was to determine the effect of classical music therapy intervention on blood pressure and sleep quality in elderly people with hypertension. This research method used a pre-experimental design with a one-group pre-post test design. The population in this study was 46 respondents. Sampling was carried out using a total sampling technique. The results of the study obtained a non-parametric statistical test (Wilcoxon sign-rank test) with a p-value of 0.000 (<0.05), indicating an effect of classical music therapy intervention on blood pressure and sleep quality in the elderly. It is hoped that the results of this study can be used as a reference and as an option for non-pharmacological therapy for the management of hypertension and sleep disorders.